Periocular Skin Warming Promotes Sleep Onset Through Heat Dissipation From Distal Skin in Patients With Insomnia Disorder - Ichiba, Tomohisa; Kawamura, Aoi; Nagao, Kentaro; Kurumai, Yuichi; Fujii, Akio; Yoshimura, Atsushi; Yoshiike, Takuya; Kuriyama, Kenichi (Frontiers in Psychiatry, 2022)
Study Objectives Periocular skin warming before bedtime has been demonstrated to improve subjective sleep initiation in healthy adults with sleep difficulties scored six or higher in the Pittsburgh Sleep Questionnaire Index. This study aimed to investigate the effects of periocular skin warming on sleep initiation and thermoregulation processes in patients with insomnia disorder. Methods Participants included those with sleep difficulty (n = 22) and those with insomnia disorder (n = 16). Individuals from both groups were assessed at baseline (habitual sleep-wake schedule) and after two intervention conditions (use of a warming eye mask or a sham eye mask before habitual bedtime). The subjective and electroencephalographic sleep onset latency, along with proximal and distal skin temperature after periocular skin warming, were evaluated. Results Periocular skin warming reduced objective sleep onset latency in independently of the group. Foot temperature and foot-proximal temperature gradient after getting into bed increased with periocular skin warming in independently of the group. However, the increase in hand temperature was observed only in the insomnia disorder group. Periocular skin warming also increased the normalized high frequency component of heart rate variability in independently of the group. The reduction of objective sleep onset latency was strongly associated with heat dissipation from the foot skin region. Conclusion These results suggest that periocular skin warming promotes sleep initiation by enhancing heat dissipation from the distal skin regions in individuals with sleep difficulty and insomnia disorder. Periocular skin warming could thus be a novel non-pharmacological therapy for insomnia disorder.